Assessing the impact of perioperative blood transfusions on the survival of adults undergoing cytoreductive surgery with hyperthermic intraperitoneal chemotherapy for appendiceal carcinomatosis. Issue 6 (14th June 2017) - Owusu‐Agyemang, P.; Zavala, A. M.; Williams, U. U.; Van Meter, A.; Soliz, J.; Kapoor, R.; Shah, A.; Hernandez, M.; Gottumukkala, V.; Cata, J. P.
Abstract : Background and Objectives: Perioperative red blood cell transfusions (PBT) may be associated with worse survival. In this study of adults undergoing cytoreductive surgery with hyperthermic intraperitoneal chemotherapy (CRS‐HIPEC), we investigated whether there was an association between PBT and survival. Materials and Methods: A retrospective study of adults who had undergone CRS‐HIPEC for appendiceal carcinomatosis was conducted. Univariate and multivariate analyses were used to identify factors associated with survival. Results: Of the 270 patients analysed, 170 (63%) received PBT. A PBT was not significantly associated with recurrence‐free survival (RFS) (HR = 1·03; 95% CI: 0·7–1·51; P = 0·879) or overall survival (OS) (HR = 0·65; 95% CI: 0·38–1·11; P = 0·116). Higher number of PBT units (≥5) was not associated with worse RFS ( P = 0·077) or OS ( P = 0·079). Independent predictors of poor survival included as follows: estimated blood loss and high tumour grade for RFS (both P < 0·001), and male gender ( P = 0·029) and high tumour grade ( P < 0·001) for OS. Higher preoperative haemoglobin was independently associated with better RFS ( P = 0·011) and OS ( P = 0·006). Conclusions: In this retrospective study of adults who had undergone CRS‐HIPEC for appendiceal carcinomatosis, PBT was not significantly associated with survival.